2010
DOI: 10.1016/j.biomaterials.2010.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of active DNA/cationic polymer polyplexes into hydrogel scaffolds

Abstract: The effective and sustained delivery of DNA and siRNAs locally would increase the applicability of gene therapy in tissue regeneration and cancer therapy. One promising approach is to use hydrogel scaffolds to encapsulate and deliver nucleotides in the form of nanoparticles to the disease sites. However, this approach is currently limited by the inability to load concentrated and active gene delivery nanoparticles into the hydrogels due to the severe nanoparticle aggregation during the loading process. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 40 publications
0
105
0
Order By: Relevance
“…1 showed entrapped pDNA into hydrogel in different chitosan/ PVP ratios. In many studies, naked or complexed DNA have been incorporated into hydrogel scaffolds such as chitosan and co-polymers with its PEG and other polymers (11)(12)(13)(14). Lei et al studied with the incorporation of active DNA/ PEI polyplexes into hydrogel scaffolds (14).…”
Section: Electrophoretic Studymentioning
confidence: 99%
See 1 more Smart Citation
“…1 showed entrapped pDNA into hydrogel in different chitosan/ PVP ratios. In many studies, naked or complexed DNA have been incorporated into hydrogel scaffolds such as chitosan and co-polymers with its PEG and other polymers (11)(12)(13)(14). Lei et al studied with the incorporation of active DNA/ PEI polyplexes into hydrogel scaffolds (14).…”
Section: Electrophoretic Studymentioning
confidence: 99%
“…In many studies, naked or complexed DNA have been incorporated into hydrogel scaffolds such as chitosan and co-polymers with its PEG and other polymers (11)(12)(13)(14). Lei et al studied with the incorporation of active DNA/ PEI polyplexes into hydrogel scaffolds (14). Tokatlian et al encapsulated VEGF gene containing plasmid into porous hyaluronic acid hydrogels to investigate scaffold-mediated local gene delivery in diabetic wound model (15).…”
Section: Electrophoretic Studymentioning
confidence: 99%
“…This can be explained by the fact that HA improves cell targeting by binding to CD44 expressed by many cell types including human MSCs at their surface. It also reduces the toxicity of PEI because the cationic amine groups from PEI are combined with the carboxylic groups present in HA resulting in higher cell viability levels 146 . The perfect synthetic polymer-based vector has yet to be found.…”
Section: Synthetic Polymer-based Transfectionsmentioning
confidence: 99%
“…77 However, the delivery of DNA through a synthetic cationic polymer ("polyplexes") hydrogel has not previously succeeded because of high aggregation and inactivation of the cationic polymer inside the hydrogel matrix. 78 But, the same polymer hydrogel when functionalized with Fbg, could be effectively used to deliver concentrated DNA without aggregation. 62 Osathanon et al reported a novel method of constructing a calcium phosphate-Fbn hydroxyapatite-based composite scaffold, which revealed a tightly interconnected network and a more porous structure, and the biodegradable composite supported primary osteoblast-like cell adhesion, proliferation, and differentiation in bone tissue engineering, in vitro and in vivo.…”
Section: Fbg and Fbn Tubes As Vascular Graftmentioning
confidence: 99%